Price, Quality, and Availability Factors on Consumption Intention of Healthy Food - Kusdiyanto, Kusdiyanto; Purwo Saputro, Edy; Irawati, Zulfa; Murwanti, Sri; Irmawati, Irmawati; Probowati Setyaningrum, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The food people consume and how the food is consumed are essential determinants of health.Consumption of healthy food is an intriguing topic with contradictory findings in various cases. It provides an indirect overview of the diversity and interest in the study of healthy food products throughout both pandemic and endemic periods. Using regression analysis, this study examined the influence of price, quality, and availability on the purchase intention of healthy food products of 100 students. The results revealed that price, quality, and availability influenced the intention to purchase healthy food products. Limitations and suggestions for further studies are offered for consideration.